Revitalization of the Kaili Language Among Primary and Middle School Students in Palu City Indonesia - Syamsuddin; Budiman, Mohammad Rizki (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
The Kaili language, spoken by the majority in Central Sulawesi, is in a critical condition, with a declining number of speakers, especially among students. Consequently, revitalization efforts are needed, particularly at the elementary and middle school levels in Palu City. This study aims to explore the process of revitalizing the Kaili language among these students. A qualitative research method was employed, with data collected through visits to several elementary and junior high schools in Palu City. Interviews with school principals were conducted and recorded using a cellphone. The findings indicate that the revitalization of the Kaili language among students in Palu City has not yet achieved optimal results. However, initiatives by the schools, the Central Sulawesi Language Center, and the Palu City government are gradually fostering students' willingness and interest in learning the Kaili language.